Legal Framework and Practical Effectiveness of Prenuptial Agreements in Indonesian Marriages - Khairun Nisa, Raden Roro Salma Almira; Tjempaka, Tjempaka (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
In the context of marriage in Indonesia, the term